Pengaruh Karakteristik Perusahaan dan Auditor terhadap Keterlambatan Audit dengan Kualitas Audit sebagai Variabel Moderasi - Susanto, Androni; Serly, Serly; Karen, Karen (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
This research was conducted to determine the influence of company and auditor characteristics on audit report lag, moderated by audit quality. The population in this study is all consumer cyclicals and non-cyclicals sector companies listed on the IDX for the period 2018 to 2022. Purposive sampling technique is one of the techniques used when determining the sample, and there are 151 entities that meet the criteria that have been determined with a period of five years, so the number of samples produced was 755 samples. Then there are 74 outlier data that will be deleted, so the total 681 samples were tested in this research. The Moderating Regression Analysis (MRA) method was used to analyze the data in this research. The results of this research indicate that audit committee effectiveness, auditor reputation, accounting complexity, and financial condition do not significantly influence audit report lag. Profitability has a significant negative effect and audit tenure has a significant positive effect on audit report lag. Audit quality unable to moderate the influence of the independent variable on the dependent variable.